How much will Herceptin really cost?. Issue 7578 (23rd November 2006) - Barrett, Ann; Roques, Tom; Small, Matthew; Smith, Richard D
Abstract : New guidance from the National Institute for Health and Clinical Excellence recommends Herceptin in early breast cancer, but it provides no additional funding or any suggestion of which services to cut. This leaves medical staff with difficult decisions to make